Pareto Superior Dimension of Rotating Savings and Credit Associations (Roscas) In Ghana - Amankwah , E. (University Of Ghana, 2017)
This thesis investigates characteristics of Rotating savings and credit associations (ROSCAs) participants who join the association due to its Pareto superior allocation in Ghana. Some scholars like Dejene and Van den Brink have hypothesized that people join ROSCAs because of its Pareto superior allocation.GLSS6 dataset was employed to look at the relationship between accounts held in formal financial and accounts held in informal financial institutions (Susu schemes was used as a proxy for ROSCA whereas commercial banks and rural banks were used as proxies for formal financial institutions with savings accounts and fixed deposits accounts as accounts held in these formal financial institutions). It was found that formal financial institutions are inversely related to informal financial institutions, hence they are substitutes. Savings accounts were also found to have a positive relationship with savings held in ROSCAs. The thesis also employed primary data analysis in achieving its main objective. Out of the 400 ROSCA participants sampled for the study from Asunafo North Municipality, 71.75% joined the association because of its Pareto superior allocation. A Probit model was used to predict the probability of joining the association due to its superior allocation. The dependent variable took the value of one when respondents join the association due to its superior allocation and zero if otherwise. Married participants, participants with no or low level of education, participants who are unemployed and participants who save more of their income are more likely to join ROSCA due to its Pareto superior allocation. It was recommended that that ROSCA participants who have access (participants living in urban sectors) to formal financial institutions, participants who have accounts at formal financial institutions, participants who are rich and aged participants should be educated on how ROSCA constitutes its Pareto superior allocation.
Keywords: Pareto Superior Dimension; Rotating Savings; Credit Associations; ROSCAs